2015
DOI: 10.1017/s1368980015001767
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices and policies in WHO European Region Member States

Abstract: ObjectiveTo provide an update on current practices and policy development status concerning breastfeeding in the WHO European Region.DesignNational surveys and studies conducted by national health institutions were prioritized. Sub-national data were included where no national data or studies existed. Information on national breastfeeding policies was collected mainly from the WHO Seventh Meeting of Baby-Friendly Hospital Initiative Coordinators and European Union projects. Owing to the different data sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 33 publications
9
79
2
1
Order By: Relevance
“…Overall, our findings on breastfeeding practices confirm the results from earlier studies [8-12, 14, 19, 42]; there are slow improvements in breastfeeding practices, low proportions of exclusive breastfeeding (both under 6 months and at 6 months of age) and wide between-country disparities in breastfeeding prevalence rates. Indeed, some of the differences between countries are striking.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, our findings on breastfeeding practices confirm the results from earlier studies [8-12, 14, 19, 42]; there are slow improvements in breastfeeding practices, low proportions of exclusive breastfeeding (both under 6 months and at 6 months of age) and wide between-country disparities in breastfeeding prevalence rates. Indeed, some of the differences between countries are striking.…”
Section: Resultssupporting
confidence: 89%
“…Despite the consistent flow of research evidence showing the health benefits from breastfeeding, along with numerous policy initiatives aimed at promoting optimal breastfeeding practices, adoption of exclusive breastfeeding remains below global recommendations [13]. In agreement with previous data from this WHO Region [19], these findings confirmed that only 4 out of 12 countries had a ≥25% prevalence of exclusive breastfeeding (for ≥6 months), namely Georgia (34.6%), Kazakhstan (50.7%), Turkmenistan (56.9%) and Tajikistan (73.3%).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations